2017
DOI: 10.1021/acs.est.7b01756
|View full text |Cite
|
Sign up to set email alerts
|

Group Contribution Approach To Predict the Refractive Index of Pure Organic Components in Ambient Organic Aerosol

Abstract: We introduce and assess a group contribution scheme by which the refractive index (RI) (λ = 589 nm) of nonabsorbing components common to secondary organic aerosols can be predicted from the molecular formula and chemical functionality. The group contribution method is based on representative values of ratios of the molecular polarizability and molar volume of different functional groups derived from data for a training set of 234 compounds. The training set consists of 106 nonaromatic compounds common to atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The values of RI and density in the limit of pure solute (no water) are estimated using both methods 1 and 3, outlined above, with values for RI (1.464 and 1.463, respectively) and density (1.355 and 1.351 g·cm –3 , respectively) in good agreement. For fits to aqueous solutions, these values provide estimates for the subcooled melts, rather than the crystalline phase, and can be considerably less than the values for the corresponding pure solids. ,, A similar comparison is shown for mixture 7 in Figure S1, again with excellent agreement between the two methods across the entire MFS range.…”
Section: Resultssupporting
confidence: 92%
“…The values of RI and density in the limit of pure solute (no water) are estimated using both methods 1 and 3, outlined above, with values for RI (1.464 and 1.463, respectively) and density (1.355 and 1.351 g·cm –3 , respectively) in good agreement. For fits to aqueous solutions, these values provide estimates for the subcooled melts, rather than the crystalline phase, and can be considerably less than the values for the corresponding pure solids. ,, A similar comparison is shown for mixture 7 in Figure S1, again with excellent agreement between the two methods across the entire MFS range.…”
Section: Resultssupporting
confidence: 92%
“…Unlike the cumulative data set, the results indicate that a linear model can yield fairly good performance in predicting n for simple case studies, with adjusted R 2 values ranging between 0.45 and 0.96. Other work has shown that at least for the organic fraction of aerosol, models relying on quantitative structure‐property relationships (Redmond & Thompson, ) and group contribution approaches are promising (Cai et al, ). However, these methods require information about the aerosol that is difficult to obtain for the complex organic fraction of ambient aerosol with field measurements, such as molecular formula, chemical functionality, and density.…”
Section: Resultsmentioning
confidence: 99%
“…MSA is produced predominantly from the oxidation of dimethylsulfide (DMS) emitted from oceans (Bates et al, 2004;Davis et al, 1998;Kerminen et al, 2017), but it also can be linked to biomass burning, urban, and agricultural emissions (Sorooshian et al, 2015). Sources of organic acids include primary emissions from biomass burning, biogenic activity, and the combustion of fossil fuels (Kawamura and Kaplan, 1987) and secondary formation via gas-to-particle conversion processes stemming from both biogenic (Carlton et al, 2006) and anthropogenic emissions (Sorooshian et al, 2007b). Secondary processing can include both aqueous-phase chemistry in clouds (Blando and Turpin, 2000;Ervens, 2018;Ervens et al, 2014;Hoffmann et al, 2019;Rose et al, 2018;Sareen et al, 2016;Warneck, 2005) and photo-oxidation of volatile organic compounds (VOCs) in cloud-free air (Andreae and Crutzen, 1997;Gelencsér and Varga, 2005).…”
Section: Introductionmentioning
confidence: 99%